Pengaruh Jenis Solubility Promotor dan Waktu Reaksi pada Sintesis Î±-Terpineol dari Minyak Terpentin menggunakan Katalis Zeolit Alam Lampung Teraktivasi - Hasanah, Nur; Putriani, Eka Nanda; Utami, Herti; Br. Ginting, Simparmin (Indonesian Journal of Chemical Science, 2019)
Turpentine is one of the essential oils that is produced in Indonesia.The main content of turpentine is Î±-pinene that can be synthesized into Î±-terpineol. This product will give a higher selling value than sells turpentine directly.The purpose of this study was to determine the effect of a kind of solubility promotor and reaction time on the hydration of Î±-pinene to produce Î±-terpineol with natural zeolite catalyst (ZAL). The zeolite before being used as a catalyst, it was activated to remove the impurities and to increase the acidity. In order to know the characteristics of zeolites were analyzed using X-Ray Fluorescence (XRF) and Fourier Transform Infrared (FTIR). In this study, the variables used were solubility promotors (isopropyl alcohol and ethanol) and reaction times (60, 120, 180, 240 and 300 minutes). The synthesis was carried out in a three-neck round bottom flask at 83Â°C , 20 mL of turpentine, 108 mL aquadest and 80 mL of solubility promotor. Compound the products of the reaction were analyzed using GC and GCMS. The results of this study showed that the highest conversion of 38.62% with the solubility promotor was ethanol at a reaction time of 300 minutes.